SAT0332 A high-dimensional approach to dissecting the role of the tissue microenvironment in shaping the immune response in psoriatic arthritis. (12th June 2018) - Chan, J.H.S.; Leung, Y.Y.; Fong, W.; Yeo, Y.W.K.; Paleja, B.; Lai, L.; Saidin, S.; Chua, C.; Nur Hazirah, S.; Poh, S.L.; Low, H.L.A.; Albani, S.
Abstract : Background: Psoriasis (Ps) currently inflicts 2%–3% of the population globally and one-third of patients have psoriatic arthritis (PsA). Up to 30% of PsA patients with active psoriasis (Ps) do not respond adequately to any treatment. Understanding the immune mechanisms contributing to the initiation and disease progression of PsA and Ps is crucial for devising novel therapeutic strategies. Objectives: To address the current unmet clinical need and bridge the knowledge gap in the pathogenesis underlying PsA/Ps, we perform transcriptomic analyses of the skin microenvironment and deep immunophenotyping of immune cells from PsA patients with active disease. We hypothesise that the interaction between the tissue microenvironment and the peripheral immune system dictates the immune response that impacts upon the development and progression of PsA/Ps. This multi-dimensional strategy will also enable the distillation of immune cell subsets in the periphery that can potentiate pathogenic responses in the microenvironment. Methods: Total RNA was extracted from skin punch biopsies of lesional and morphologically normal sites from 7 patients with active disease. RNASeq was performed to decipher the transcriptomes of the skin punch biopsies. Peripheral Blood Mononuclear Cells (PBMCs) from 17 PsA patients and 12 healthy donors were stimulated with PMA-Ionomycin, stained with 37 phenotypic T cells markers and interrogated with the CyTOF platform. Dimensional reduction and unsupervised clustering analyses were performed with Multi-dimensional Automated Reduction and Visualisation (MARVis). Results: Transcriptomic analysis of skin punch biopsies of psoriatic and morphologically normal sites revealed a gene signature in lesional skin that promotes the infiltration of multiple immune cell subsets into the microenvironment. The expression of chemokine genes such as CXCL8, CCL4, and CCL20 suggests a role for the accumulation of neutrophils, monocytes, natural killer (NK) cells and lymphocytes in the establishment of a pro-inflammatory microenvironment that is perpetuated by the presence of TNF and IFNγ. Examination of the immune landscapes of PsA patients highlights multiple perturbations in various immune cell subsets. Specifically, we observed declines in CD8 +CD161+TCRVα7.2+Mucosal Associated Invariant T (MAIT), CD4 +CD45RO+CXCR5+TFH as well as CD45RO+Tbet+IFNγ+TNFα+IL17A+memory TH1 cells in PsA patients. This decline is potentially attributed to the trafficking of these immune cell subsets into the microenvironment in response to chemokine signals. Conversely, we observed enrichments of CD56 +Tbet+GranB +IFNγ+NK and activated CD4 +CD127+CCR7+CD69+effector T cells in PsA patients that can contribute to the pathogenic immune response. Conclusions: Our multi-dimensional approach resolves the complex interactions between the tissue microenvironment and the peripheral immunome that shapes the immune response and dictates the cellular composition in lesional skin. These findings possess translational value and will facilitate the identification of novel immune therapeutic targets. Disclosure of Interest: None declared